Experimental and numerical study of the acoustic performance of a novel composite core thermal break - Tran-Van Han; Gayoon Lee; Yun-Seong Shin; Sungwoo Woo; Kihak Lee (Case Studies in Construction Materials)
This study assesses the acoustic performance of a novel thermal break system with composite cores through both experimental testing and Finite element (FE) analysis. The research explores the effects of varying the thicknesses of key materials, including Expanded Polystyrene (EPS), Cellulose Fiber Reinforced Cement (CRC) boards, and Melamine foam, on sound insulation while maintaining a constant overall thickness of the thermal break. Results show that reducing EPS thickness and increasing CRC or Melamine foam thickness by 12 mm, along with strategic layering of Melamine with CRC boards, enhances sound insulation by 2–5 decibels (dB). The configuration with the thickest Melamine foam layer achieved the highest sound insulation improvement, ranging from 2 to 6 dB over other configurations. Additionally, FE vibro-acoustic analysis proved to be a reliable predictor of acoustic performance, closely aligning with experimental data. A parametric study further revealed a nearly linear correlation between EPS layer thickness and sound insulation efficacy. These findings underscore the crucial role of material selection and strategic layering in designing thermal breaks that effectively balance sound and thermal insulation, contributing to improved environmental quality and occupant comfort in buildings.